Effects of Contamination of Freshwater Habitat With Common Heavy Metals and Anions on the Prevalence of Human Adenoviruses and Enteroviruses - Michael Opere Wasonga; John Maingi; Ombori Omwoyo (Frontiers Media S.A., 2021)
The occurrence and survival of enteric viruses in open surface waters can be impacted by a host of factors including fecal emission levels, seasonal variations, virus stability and the physicochemical parameters. In this research, we aimed to document the association between contaminations of water samples with human enteric viruses (adenoviruses and enteroviruses) from a freshwater lake with variations in chemical contaminants. We collected 216 water samples from October 2010 to April 2012, from a 4 km stretch along Lake Victoria (LV) basin in Homa Bay town located in the western region of Kenya. The samples were analyzed for the existence of human adenoviruses (HAdV) and human enteroviruses (HEV), using the nested PCR (nPCR). We also assessed in the water samples the levels of twelve chemical contaminants consisting of six heavy metal elements and six anions. About 8.3 % of the samples were found to be contaminated with the enteric viruses. The concentrations of the 12 chemical contaminants were found to be largely within the WHO suggested limits. Most of the chemical contaminants were not related to the detection rates of the viruses from the statistical analysis. However, some positive and negative associations between the viral genome's detection and the chemical concentrations were established for only three metals (Fe, Pb, Cd) and the PO43− Radical. Cd had a weak positive significant relationship with HAdV (rho = 0.146, p = 0.032) while Pb and Fe had a weak positive significant relationship with HEV genome detection (rho = 0.156, p = 0.022) and (rho = 0.148 and p = 0.029) respectively. There was a modest negative relationship between phosphate ions and HEV (rho = −0.174, p = 0.010). The results of our study do not provide support for the hypothesis of an association between the presence of human enteric viruses and the levels of twelve chemical contaminants.